Reflexion Sur Les Enjeux Epistemologique Et Methodologique De L’approche Anthropologique Sur La Maladie Chronique En Contexte Africain A Travers L’exemple Du VIH/Sida - Kouame Atta (European Scientific Journal, ESJ, 2017)
Our practical experience of anthropology in the field of HIV/AIDS and many researchers’ commitment in such scientific programs showed that social sciences’ approach of chronic disease in African cultural context includes relevant epistemological and methodological issues. The purpose of this article is to give an overview of these issues while showing the contribution of the anthropological approach to the comprehension of the health phenomena related to the AIDS in the African environment. The approach to this was to review the literature on fieldwork already done on HIV / AIDS in the social sciences. The results of our analysis indicate that medical research on HIV / AIDS in African cultural context has mobilized social sciences mainly anthropology in its various specialties which alongside Biology, Epidemiology and Clinic have led to the development of an inclusive approach of the disease. This interactive approach between social sciences and medical sciences allowed fulfilling the limits of medicine’s quantitative approaches and thus to grasp the AIDS pandemic in these epidemiological, behavioral and representational aspects.